Country Brand: a critical reading for Latin America inspired by the philosophy of Well Living - Canelón Silva, Agrivalca Ramsenia (2017)
The article presents an analysis on the concept of Country Brand from a critical perspective, resorting to revision of a theoretical and documentary sort, aimed at establishing its key defining and distinctive elements backgrounded by its development and technical implementation, considering the specificity of its nature as a semiotic entity in the field of communication and culture. On this grounds, a brief analysis is proposed, under which its potentialities, scope, limitations and even distortions from the perspective of the “Well Living” philosophy are examined, taking as scope of application the case of Latin America and the Caribbean.